2022
DOI: 10.1186/s13071-022-05532-z
|View full text |Cite
|
Sign up to set email alerts
|

Thelazia lacrymalis in horses from Romania: epidemiology, morphology and phylogenetic analysis

Abstract: Background Equine thelaziosis is a neglected vector-borne parasitic disease in modern veterinary medicine, lacking recent reports. It is transmitted by Musca autumnalis, and potentially other Muscidae species, by ingesting the lachrymal secretions of its equine host. The distribution of both Thelazia lacrymalis and its intermediate hosts remains largely unknown throughout Europe, with most studies dating back 20 years. The aim of this study was to assess the presence, prevalence and distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…9 A and B; Supplementary Fig. S3A and B ) ( Cotuțiu et al., 2022 ) and sample sequences sets into the same SD for sequence alignment using offline software such as MEGA. This approach facilitated an intuitional and rapid assessment of the identity and differences of nucleotide sites within one SD ( Cotuțiu et al., 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…9 A and B; Supplementary Fig. S3A and B ) ( Cotuțiu et al., 2022 ) and sample sequences sets into the same SD for sequence alignment using offline software such as MEGA. This approach facilitated an intuitional and rapid assessment of the identity and differences of nucleotide sites within one SD ( Cotuțiu et al., 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that the widespread occurrence of M. domestica and M. autumnalis in the natural and semi-natural environment may result from them being synanthropic fly species connected with livestock husbandry 40 . Although it has been suggested that M. domestica may play a role in Thelazia transmission 8 , M. autumnalis is considered the main vector 43 and might participate in passing the infection between sylvatic and synanthropic ruminant species. As there are no current data of Thelazia occurrence in other wild and domestic ruminants in Poland, it is important to begin regular eyeworm monitoring in areas known to be at risk of thelaziosis in European bison.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the biodiversity of flies (Diptera) was conducted in different ruminant farming systems in Poland (Nosal et al, 2019). Moreover, studies in farms in Romania have investigated the role of the intermediate host Musca autumnalis (M. autumnalis) in the spread of equine thelasiosis (Cotuțiu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%